2018
DOI: 10.1002/adom.201701346
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Mid‐Infrared Phase‐Change Metasurface

Abstract: reduce the size of these sensors, [4][5][6][7][8][9][10][11][12] since it exhibits a unique surface condition with tailored spectral properties and strong electric field enhancement, which results in a high sensitivity to the surroundings. [13][14][15][16][17][18][19][20][21] To date, most approaches toward metamaterial inspired sensors are based on perfect light absorption. [17,19,22,23] However, the measurement of their reflectance makes both optical alignment and chip integration challenging. [24] Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 69 publications
1
75
0
Order By: Relevance
“…Commonly, active infrared MSs based on PCMs exhibit different operation states by switching the entire MS via heating and short electrical or optical pulses . Intermediate states of the PCM crystallization have also been exploited to obtain partial resonance shifts by adjusting the annealing conditions.…”
mentioning
confidence: 99%
“…Commonly, active infrared MSs based on PCMs exhibit different operation states by switching the entire MS via heating and short electrical or optical pulses . Intermediate states of the PCM crystallization have also been exploited to obtain partial resonance shifts by adjusting the annealing conditions.…”
mentioning
confidence: 99%
“…It can be observed that the trend of the Q ‐factor at ω 1 shows a linear increase with a maximum value of 50. The abovementioned electromagnetic performance is better than that obtained for other THz‐metamaterial devices reported in the literature . This result can be explained by the field distributions for the PSM in the TE and TM modes, as shown in Figure c.…”
mentioning
confidence: 61%
“…There have been many novel inventions that have been greatly improved by using a THz metamaterial to replace classic devices, such as waveguides, resonators, filters, polarizers, and switches . To make a THz metamaterial more flexible and applicable, some progress has been made in the realization of controlling THz waves by using optical, electrical, magnetic, and thermal approaches. Among these approaches, a reconfigurable metamaterial becomes feasible in the active manipulation of THz wave applications.…”
mentioning
confidence: 99%
“…Compared with other phase change materials, the well‐established technique of GST fabrication is already amenable to hybridization due to the high quality GST thin films which can currently be obtained through magnetron sputtering using argon as the sputtering gas. Although optically triggered phase transition was reported in an early study, tuning of GST‐hybrid metasurfaces has been primarily achieved through direct thermal control . In particular, the large change in refractive index of GST has been used to tune a variety of metasurface properties, including nanoantenna resonance characteristics, absorption/emission properties, chirality, and phase discontinuities among others.…”
Section: Phase Change Materialsmentioning
confidence: 99%